A Review of Scale Development Practices in the Study of Organizations - Hinkin, Timothy R. (Journal of Management, 1995)
Questionnaires are the most commonly used method of data collection infield research (Stone, 1978). Problems with the reliability and validity of measures used on questionnaires has often led to difficulties in interpreting the results of field research (Cook, Hepworth, Wall & Wart-, 1981; Schriesheim, Powers, Scandura, Gardiner & Lankau, 1993). This article reviews scale development procedures for 277 measures used in 75 articles published in leading academic journals from 1989 to 1994. It points out some of the problems encountered and provides examples of what could be considered “best practices “in scale development and reporting. Based on the review, recommendations are made to improve the scale development process.